Damage from proton irradiation of vertical-cavity surface-emitting lasers - Warren, Mial E., author; Lear, Kevin L., author; Hou, Hong Q., author; Choquette, Kent D., author; Taylor, Edward W., author; Schöne, Harald, author; Carson, Richard F., author; Paxton, Alan H., author; IEEE, publisher (Colorado State University. Libraries, 1997)
Damage resulting from irradiating oxide-confined vertical-cavity surface-emitting lasers became significant (threshold shift ≈ 20%, peak power degradation ≈ 20%) at fluence levels approaching 1 × 1013 protons/cm2. The threshold current shifted to higher values, and the peak light output power decreased. Forward-current annealing led to partial recovery of the performance of two of the three lasers for which annealing was attempted. Recent results [1-3] on proton-implanted devices are summarized in a table.
Keywords: proton effects; semiconductor lasers; laser reliability; annealing; surface emitting lasers